“Interethnic Interaction in Multicultural Educational Space: Problems of Language Interaction and Intercultural Communication” - All-Russian Scientific and Practical Conference - S. L. Mikheeva (Научный диалог, 2018)
The article presents an overview of the results of the all-Russian scientific and practical conference “Interethnic interaction in multicultural educational space: problems of language interaction and intercultural communication,” held on November 26-27, 2018 at the Chuvash Sate Pedagogical University named after I. Ya. Yakovlev (Cheboksary, Russia). It is reported on the participants, directions of work, main provisions made in the reports.